Rangeland conversion to dryland and its effects on species diversity and richness - REZA Hasanpori; ADEL Sepehry; HOSSEIN Barani (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Hasanpori R, Sepehry A, Barani H. 2019. Rangeland conversion to dryland and its effects on species diversity and richness. Biodiversitas 20: 2043-2047.  Species diversity and richness status in ecosystem is important in confront to environmental threats and is guidance in plant management. Due to increasing land use changes and destruction of rangelands in western Iran, this research was conducted to study the effects of land use change from rangeland to dryland on species diversity and richness of vegetation cover in three land uses of rangeland, dryland and abandoned dryland. Vegetation cover data were collected from established plots in each land use. Species diversity and richness were calculated in each land use by Simpson and Shannon indices and Menhinick and Margalef ones, respectively. Results showed that these indices are significantly different at 95% level in three land uses. The highest species diversity and richness indices were in rangeland and the least were in dryland. So, we found that four above measured indices, are illustrative and accurate enough to demonstrate differences between several land-use diversity and richness. Simplification on a dynamic and diverse ecosystem, and land conversion to dryland reduced plant species numbers in the new ecosystem, and simplify species composition, so simple dryland ecosystem would be fragile against environmental threats. Therefore to reduce unfavorable effects of land use changing, paying more attention to species diversity conservation must be a base to management decisions.